Deskripsi Kemampuan Kognitif Melalui Permainan Puzzle pada Anak Kelompok B di TK Negeri Pembina Kabupaten Sorong - Tasya Ramadhani Jamal Ahary; Yolan Marjuk; Siti Hardianti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aimed to know how does puzzle game conduct in developing children cognitive in age 5 to 6 years old at TK Negeri Pembina of Sorong Regency. The result of this research indicated that there was an influence on puzzle game toward cognitive development of before and after using puzzle game. It meant that the use puzzle game can help to stimulate the childrens’ cognitive development, especially on the ability if problem solving for students in age 5 to 6 years old. For this research had function to describe the effectiveness of puzzle game ini increasing childrens’ cognitive development in age 5 to 6 years old. To collect the data, this researcy used observation sheet, interview and documentation. The result of observation sheets and interview, the research applied puzzle game to be able improve cognitive development of students class B in age 5 to 6 years old.